EFFECTS OF INTEGRATING INSTRUCTIONAL MODELS WITH LECTURE METHOD ON ACADEMIC PERFORMANCE OF STUDENTS OF SMALL CLASS-SIZE IN ZARIA EDUCATIONAL ZONE KADUNA STATE - Yusuf, Aminu (Sokoto Educational Review, 2018)
This study investigated the effects of integrating instructional models with lecture method on academic performance of students of small class-size in some Biology concepts among Senior Secondary School Students in Zaria Education Zone. Fifty students randomly selected from two Senior Secondary Schools constitute the sample for the study. The schools were grouped into two. one as experimental with 25 students and the other as control with 25 students from the total population of 4,450 S.S.S 3 students in the zone. The study adopted a pretest, posttest quasi-experimental and control group. The subjects in the experimental groups were taught by Integrating Instructional Models with Lecture while the control groups were exposed to the lecture method. A Biology Achievement Test (BAT) with Reliability Coefficient o f 0.75 was used to measure the students’ achievement after the treatment. The data collected was analysed using mean, standard deviation and t-test. Results indicated that there is a significant difference in the mean academic performance of students taught Biology concepts using Integrating Instructional models with lecture method compared to those taught using lecture method of instruction in small class size. Based on the findings it was recommended that Integrating Instructional models with lecture method should be used by Biology teachers to teach in Senior Secondary School. Biology teachers should be trained on the effective use of instructional models in Senior Secondary Schools among others.